Response of soybean to Rhizobium biofertilizer under different levels of phosphorus - Islam, MS; Ahmed, M; Hossain, MS; Akter, H; Aktar, S (Progressive Agriculture, 2018)
A field experiment was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University (BAU), Mymensingh during January to May 2015 to study the response of soybean to Bradyrhizobium biofertilizer under different levels of phosphorus on growth, yield, nutrient content and uptake by soybean. The experiment was laid out in a randomize complete block design with three replication of each treatment. The treatments were: To = Control, T1=(100% Nitrogen), T2=(Bradyrhizobium), T3=(Bradyrhizobium inoculation+75% P), T4=(Bradyrhizobium inoculation+10 P), T5=Bradyrhizobium+125% P), T6=(100% RFD+Bradyrhizobium). Potassium and Sulphur at recommended dose were applied as basal to all the treatments. Urea was applied in three spits. Phosphorus in the form of TSP was applied as per treatment during final land preparation. Soybean seeds were inoculated with Bradyrhizobium as per treatments. Intercultural operations were done as and when necessary. Data were collected on pods weight, grain and stover yields. The N and P contents in grain stover and total N and P uptake by soybean were determined. Inoculation of seeds with Bradyrhizobium and application of N and P fertilizer at recommended dose recorded the highest grain and straw yields of soybean. The results suggest that soybean cultivation can effectively be done in the Old Brahmaputra Floodplain soils by Inoculating with Bradyrhizobium biofertilizer in combination with recommended dose of N, P, K and fertilizer. Progressive Agriculture 28 (4): 302-315, 2017